All about cells - Kolb, Lisa; Krömker, Susanne (Complexity and Synergetics, 2018)
Investigating the longterm behaviour of cells in the lymph nodes releasing an activating substance into an intercellular space is a demanding task for mathematical modelling and numerical simulations of reaction-diffusion systems coupled with ordinary differential equations on unstructred 3D grids.